Moana - Bush, Jared, 1974-; Clements, Ron; Musker, John; Hall, Don, 1969-; Williams, Chris, 1971-; Shurer, Osnat; Ribon, Pamela; Kandell, Aaron; Kandell, Jordan; Cravalho, Auli'i, 2000-; Johnson, Dwayne, 1972-; House, Rachel; et al. (Los Angeles, California Walt Disney Studios Home Entertainment, 2017)
A mythic adventure set around 2,000 years ago across a series of islands in the South Pacific. The film follows the journey of a spirited teenager named Moana as she meets the once-mighty demi-god Maui, and together they traverse the open ocean, encountering enormous fiery creatures and impossible odds.
Originally released as a feature film in 2016.
Wide screen (2.39:1).
Special features: deleted song: "Warrior face"; short film "Inner workings"; Voice of the Islands; Things you didn't know about; Island fashion; The elements of ... ; They know the way: making the music of Moana; music video "How far I'll go" by Alessia Cara; deleted scenes; fishing for Easter eggs; audio commentary.
Original songs, Lin-Manuel Miranda, Opetaia Foa'i, Mark Mancina ; music, Mark Mancina ; editing, Jeff Draheim ; production designer, Ian Gooding ; art directors, Andy Harkness, Bill Schwab ; cinematography, Rob Dressel, Adolph Lusinsky.
Auli'i Cravalho, Dwayne Johnson, Rachel House, Temuera Morrison, Jemaine Clement, Nicole Scherzinger, Alan Tudyk, Oscar Kightley, Troy Polamalu, Puanani Cravalho, Louise Bush.
MPAA rating: PG; for peril, some scary images and brief thematic elements. CHV rating: PG.
Keywords: Gods -- Juvenile films; Voyages and travels -- Juvenile films; Polynesians -- Juvenile films; Oceania -- Juvenile films; Video recordings for people with visual disabilities; Video recordings for the hearing impaired; Animated films; Children's films; Fiction films; Feature films; Juvenile works; Action and adventure films